Dynamic behavior of screwed joints for CFRP composite laminate structures under impact loading. (March 2022) - Can, Ahmet; Meram, Ahmet
Abstract: The detachable joining techniques in composite laminates compared to metals are limited and assumed one of the major obstacles in developing composite structures. In prior work, the authors successfully investigated the screw joining technique for CFRP composite laminates under static loads. However, the dynamic behavior of this joining technique for composite laminates was unknown. This study was conducted to examine the dynamic behavior of the screwed joints in CFRP composite laminates. For this purpose, impact tests were performed on bolted composite laminates with metric screw sizes ranging from M6 to M14 and different pitch screws. The dynamic response of screwed joints was determined by load deflection, peak force, and failure mechanism. Macro and scanning electron microscope (SEM) images were used to analyze the damage mechanisms in detail depending on screw and pitch size. Pure stripping tests are also conducted to determine the effect of tooth root thickness on the stripping force. The damage mechanism changed from interlaminar delamination to push-out delamination as the pitch increased, and outward fibering was primarily observed in high pitches. The maximum dynamic failure loads for the screwed joints were between 27.55 and 78.12 kN.